RANCANGAN BANGUN SISTEM INFORMASI BUKU INDUK PADA SEKOLAH SMA SWASTA PERSIAPAN STABAT BERBASIS WEB - Prayoga, Ricky Dwi; Muttaqin, Muhammad (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The student master book is an important document in the school administration system that functions as the main archive of personal, academic, and student history data during their education. At SMA Swasta Persiapan Stabat, recording of master book data is still done manually using printed forms and simple spreadsheet applications. This causes various obstacles such as data duplication, difficulty in searching for information, risk of data loss, and low work efficiency of school administration staff. To overcome these problems, a web-based master book information system is needed that is able to digitize and automate the process of managing student data in a structured, integrated, and secure manner. This study uses the Waterfall model system development method which consists of five stages, namely: needs analysis, system design, implementation, testing, and maintenance. The system is built using the PHP programming language, CodeIgniter framework, and MySQL database. The main features provided include student data input, data search based on certain categories, data updates, printing master books, and automatic backup systems. System testing is carried out using the Black Box method to ensure that all functions run according to user needs. The results of this study indicate that this web-based master book information system is able to increase the efficiency, accuracy, and speed of student data management. In addition, the system also makes it easier for schools to provide valid data that can be accessed quickly when needed. This system is expected to be the first step in digitalizing administration in the school environment. Keywords: Information System, Master Book, Web, Private High School, School Administration, CodeIgniter Abstrak: Buku induk siswa merupakan dokumen penting dalam sistem administrasi sekolah yang berfungsi sebagai arsip utama data pribadi, akademik, dan riwayat siswa selama menempuh pendidikan. Di SMA Swasta Persiapan Stabat, pencatatan data buku induk masih dilakukan secara manual menggunakan formulir cetak dan aplikasi spreadsheet sederhana. Hal ini menimbulkan berbagai kendala seperti duplikasi data, kesulitan dalam pencarian informasi, risiko kehilangan data, serta rendahnya efisiensi kerja tenaga administrasi sekolah. Untuk mengatasi permasalahan tersebut, dibutuhkan sistem informasi buku induk berbasis web yang mampu mendigitalisasi dan mengotomatisasi proses pengelolaan data siswa secara terstruktur, terintegrasi, dan aman. Penelitian ini menggunakan metode pengembangan sistem model Waterfall yang terdiri dari lima tahapan, yaitu: analisis kebutuhan, perancangan sistem, implementasi, pengujian, dan pemeliharaan. Sistem dibangun dengan menggunakan bahasa pemrograman PHP, framework CodeIgniter, serta database MySQL. Fitur-fitur utama yang disediakan antara lain input data siswa, pencarian data berdasarkan kategori tertentu, pembaruan data, cetak buku induk, dan sistem backup otomatis. Pengujian sistem dilakukan menggunakan metode Black Box untuk memastikan bahwa seluruh fungsi berjalan sesuai dengan kebutuhan pengguna. Hasil dari penelitian ini menunjukkan bahwa sistem informasi buku induk berbasis web ini mampu meningkatkan efisiensi, akurasi, dan kecepatan pengelolaan data siswa. Selain itu, sistem juga mempermudah pihak sekolah dalam menyediakan data yang valid dan dapat diakses dengan cepat saat diperlukan. Sistem ini diharapkan dapat menjadi langkah awal digitalisasi administrasi di lingkungan sekolah. Kata kunci: Sistem Informasi, Buku Induk, Web, Administrasi Sekolah, CodeIgniter, Waterfall.